Salt in my footsteps - Radebe, Mxolisi Vusumuzi (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis is a collection of poems which focus on human experiences related to my background. I grew up in a countryside village, freely experiencing nature in unrestricted walks to the rivers and mountains; communal living instilled in me the humanitarian values which I uphold to the present. I use short and long lyrical prose poems to bring life and humanise the untold or unexpressed stories of my community. My use of simple everyday language and clear, concrete but surprising images that resonate with deeper meanings and emotions is influenced by Seitlhamo Motsapi's poems, especially his collection of poems titled earthstepper/the ocean is very shallow and Mxolisi Nyezwa's poetry book, Song Trials. Spanish poems in English translations by the 20th century Spanish poets: Blas de Otero, Juan Roman Jimenez and Federico Garcia Lorca, published in the book titled Roots and Wings have had a huge impact on my construction of images. I also draw from the free-form and narrative prose poetry experiments of poets: Mangaliso Buzani, vangile gantsho and Ivy Alvarez.
Keywords: Creative writing (Higher education) -- South Africa; South African poetry (English) -- 21st century; South African fiction (English) -- 21st century